2021
DOI: 10.1016/j.pmedr.2021.101617
|View full text |Cite
|
Sign up to set email alerts
|

Maternal folic acid and multivitamin supplementation: International clinical evidence with considerations for the prevention of folate-sensitive birth defects

Abstract: More evidence is available for maternal intake, absorption, distribution, tissue specific concentrations, and pregnancy outcomes with folic acid (fortification/supplementation) during preconception – first trimester. This Quality Improvement prevention review used expert guidelines/opinions, systematic reviews, randomized control trials/controlled clinical trials, and observational case control/case series studies, published in English, from 1990 to August 2021. Optimization for an oral maternal folic acid sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 224 publications
(284 reference statements)
0
25
0
1
Order By: Relevance
“…Serum folate levels of 28e30 nmol/L (red blood cell folate level >907 nmol/L) have been extensively evaluated in pregnant populations, and there is clear evidence that this maternal red blood cell folate level protects against folic aciderelated NTDs in the fetus. 10 A 2021 comprehensive review article entitled "Maternal folic acid and multivitamin supplementation: International clinical evidence with considerations for the prevention of folate-sensitive birth defects," 11 provides the clinical evidence supporting the recommendations in this guideline. There are a number of clinical considerations to ensure that pregnant women achieve optimal serum folate levels, and the risk level of the patient must be taken into account.…”
Section: Benefits Of Folic Acid Supplementation For the Prevention Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…Serum folate levels of 28e30 nmol/L (red blood cell folate level >907 nmol/L) have been extensively evaluated in pregnant populations, and there is clear evidence that this maternal red blood cell folate level protects against folic aciderelated NTDs in the fetus. 10 A 2021 comprehensive review article entitled "Maternal folic acid and multivitamin supplementation: International clinical evidence with considerations for the prevention of folate-sensitive birth defects," 11 provides the clinical evidence supporting the recommendations in this guideline. There are a number of clinical considerations to ensure that pregnant women achieve optimal serum folate levels, and the risk level of the patient must be taken into account.…”
Section: Benefits Of Folic Acid Supplementation For the Prevention Of...mentioning
confidence: 99%
“…Women who can become pregnant may have genetic, environmental, and immune factors that can affect serum levels of folate, thereby increasing the risk of NTDs and other folate-sensitive congenital anomalies and possibly requiring increased supplementation for prevention. Box 1 [10][11][12][13][14][15][16][17][18] summarizes the identified risk factors for NTDs or for low folate status in pregnancy and Table 1 illustrates the effects of medications on folate metabolism.…”
Section: Factors That Affect Folate Levels In Pregnant Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…The title is also discordant with the body of the paper, which discusses the prevention of two lowprevalence conditions-spina bifida and anencephaly-without referring to other folate-sensitive congenital anomalies (eg, cardiac anomalies, orofacial clefts, limb defects, hydrocephalus, and urinary tract anomalies). 2 The second issue is that, by calling for universal fortification, the paper fails to contextualise prevention of birth defects in the resource realities of low-income and middle-income countries (ie, only women in the preconception and interconception period are targeted, rather than the entire population). The authors overlook realities of poor access to food and diet diversity, cultural practices, and costs of fortification.…”
Section: Mandatory Food Fortification With Folic Acidmentioning
confidence: 99%
“…A recent review showed strong evidence that oral prenatal fortification and supplementation dosing of folic acid (FA) can prevent the incidence of VSD and atrial septal defect (ASD) [ 11 ]. Women with a diverse diet during pregnancy (dietary diversity score, DDS ≥5) had lower risks of having fetuses with total CHD and VSD [ 12 ].…”
Section: Introductionmentioning
confidence: 99%